MATEC Web of Conferences - Vorontsova, E. S. specialist in the field of heat and power engineering Engineer of Tomsk Polytechnic University 1990- (EDP Sciences, 2018)
In this article the research of prospects of use of low-grade brown coal of the Talovsky Deposit of the Tomsk region as fuel for local power is carried out. The study is carried out by checking calculations of the steam boiler BKZ-220-100. The result of the study is to obtain data on the parameters of the boiler during the combustion of brown talovsky coal as the main fuel, as well as in a mixture with natural gas or Kuznetsk coal.